MDPI, Frontiers et al.: Eine kritische Betrachtung von Qualitätsaspekten - Pohlmann, Tobias (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2025)
Opinions about the Open Access publishers MDPI, Frontiers and formerly Hindawi vary. Some praise them for their efficient processes and low-threshold options for publication, while others criticize their low-quality standards and questionable business practices and argue that their sole aim is to increase the number of articles published. This study attempts to characterize these publishers on the basis of numerous sources and the author’s own analyses.
Keywords: MDPI; Frontiers; Hindawi; Gray publishers; Open access